Factors influencing overweight children's commencement of and continuation in a resistance training program - Pescud, M.; Pettigrew, Simone; McGuigan, M.; Newton, R. (BioMed Central Ltd, 2010)
Background: In light of the child overweight and obesity problem in Australia, resistance training programs have been trialled as an innovative way of assisting children increase lean body mass and reduce body fat. The purpose of this study was to investigate the factors influencing overweight children’s participation in a resistance training trial program. Method: Parent-child pairs who participated in the trial program were invited to take part in a follow-up individual interview to discuss their program experiences. In total, 22 semi-structured interviews were conducted with 11 parent-child pairs. Results: The factors found to be most relevant to program commencement among parents were a desire for their child to lose weight and gain confidence, the proximity of the venue, and no cost for participation. For children, the most relevant factors were the opportunity to build strength and improve fitness and having supportive parents who facilitated program initiation. The factors most relevant to continuation for parents were the quality of the program management, being able to stay for the sessions, the child’s improved weight status, coordination, and confidence, and no cost for participation. Weight loss and improved confidence were also motivators for continuation among the children, along with pleasant social interaction with peers and trainers and ongoing parental support. Conclusion: Different factors variably influence program commencement and program continuation in both parents and children. This has important implications for future interventions that aim to successfully recruit and retain intervention participants